Adaptive finite control set model predictive control for three-phase inverters connected to distorted grid with fewer voltage sensors. (November 2021) - Li, Po; Li, Ruiyu; He, Ying; Zhang, Jingrui
Abstract: This paper proposes an adaptive finite control set model predictive control (FCS-MPC) scheme for three-phase inverters connected to distorted grid with fewer voltage sensors. For the distorted grid voltage construction, a composite observer is introduced. The observer is composed of two parts, a phase detection module and time-varying observers. The phase information is obtained by the measured voltage of one phase. Then the other two-phase grid voltage is identified by time-varying observers. The convergence of time-varying observers is guaranteed by a Lyapunov function and the Lasalle invariance principle. Moreover, the outputs of the observer are the DC component and the amplitude of each harmonic, which is helpful to obtain positive components without complex post-processing. Finally, the FCS-MPC scheme with simplified cost function is employed for current tracking in natural ( a b c ) coordinate rather than α β coordinate. Simulation on Matlab/Simulink and experiments on FPGA platform for the three-phase inverter under distorted grid conditions prove that the proposed control approach can perform well with fewer voltage sensors. Highlights: Use time-varying observers to achieve the purpose of reducing grid voltage sensors. The proposed observer can still respond quickly when the fundamental wave fluctuates. The cost function of FCS MPC is simplified to natural (abc) coordinates. The proposed controller is validated by FPGA rapid control prototyping platform.